The Effectiveness of Indonesian Government Assistance in Handling and Breaking Covid-19 Chains - Tessa Septy Dynesia (Universitas Negeri Semarang, 2020)
In response to Corona Virus issues, the government has increased security so that Indonesian people can comply with and follow orders from the government, such as self-quarantine in the home or regional provinces, districts and districts. But it also doesn't keep all societies in compliance with the rules, there's a rogue society and it's as if it won't be infected by the corona virus and they still go about outdoors without wearing masks. As for the start of government policy in dealing with a corona virus is lockdown. Because of the notion that lockdown has failed to address corona, governments select large-scale social restrictions (PSBB). The government has made sure no more state quarantine or lockdown but has implemented PSBB to suppress the spread of corona. One reason the government does not implement a region quarantine is that it is obliged to address basic social needs during these stages. Governments are also obliged to pay for livestock during the quarantine as indicated in the 55-year 2018 bill on health quarantine. Furthermore, governments have also seen the failure of territorial quarantine policies across countries. Large-scale social restrictions (PSBB) have been applied to the 2007 2007 law on disaster relief and health legislation no.6. Large-scale social restrictions will also refer to the civil emergency policy of no.23 years of 1959 policy on the state of danger.